(untitled) (Research, Society and Development, 2020)
The work presents results of research that aimed to discuss issues related to hereditary succession, seeking to understand it, based on the characterization of the sons and daughters of family farmers, their prospects for staying in rural areas and in agriculture. The research is comprised of Vicinal 12, municipality of Brasil Novo, illustrative of family farming in the Transamazônica region, planned occupation area of the 1970s. The study was carried out through observations and interviews (semi-structured and open) conducted with twenty families, where parents and children were interviewed separately in the first semester of 2014. The data collected were systematized through transcriptions and tabulation of the data in a spreadsheet. Among the main results, it was highlighted that out of twenty families interviewed, only five had already transferred the property to the successor, or were in the transmission phase. There was also a lack of perspective for continuity of work in agriculture by the young population of the community, which can compromise the issue of succession in family farming.